Regulation of static and dynamic balance in healthy young adults: interactions between stance width and visual conditions - Luo, Wei; Huang, Zhirui; Li, Hao; Zhong, Tao; Chen, Peishun; Min, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThis study investigates the impact of five distinct stance widths on static balance and limits of stability in healthy adults under varying visual conditions, specifically with eyes open and closed.MethodsThe Prokin Balance Instrument was used to evaluate static balance with both eyes open and closed, as well as limits of stability with eyes open, in 20 healthy adults (male, age = 21.55 ± 1.39). Participants were assessed at five stance widths (0 cm, 10 cm, 20 cm, 30 cm, and self-selected width) for each condition. Statistical analysis of the test indices was conducted using repeated measures ANOVA.ResultsIn static balance tests, index values were higher with eyes closed than with eyes open, with this difference being most pronounced at narrower stance widths. Notably, a significant main effect was observed for all indicators, in the static balance test under varying visual and stance width conditions (P < 0.001). Significant interactions between visual conditions and stance width were identified for all static balance indicators (P < 0.001), except for average speed of anteroposterior sway (P = 0.195). Across both visual conditions, static balance indicators displayed a U-shaped distribution (a decrease followed by an increase) with increasing stance width, reaching a minimum at the self-selected width (16.35 ± 4.20 cm) and 20 cm. Additionally, significant main effects were observed for limits of stability in both the anteroposterior and mediolateral directions (P < 0.001). The limits of stability in the anteroposterior and mediolateral directions increased monotonically with stance width, peaking at 30 cm. The influence of stance width on static balance and limits of stability was significantly greater in the mediolateral direction compared to the anteroposterior direction, regardless of visual condition.ConclusionAs stance width increases, the reliance on visual input for maintaining static balance decreases in healthy adults. We recommend using a self-selected stance width to optimize static balance and a 30 cm stance width to achieve maximum limits of stability during postural assessments.